How to engage Children and Families as Part of Multidisciplinary Health Promotion Teams - Macnab, Andrew John (GHMJ (Global Health Management Journal), 2024)
Health promotion is the process we employ as health care providers and policy makers to enable people to increase control over, and to improve, their health. Effective health promotion includes several major components, and while policies must be made to promote health, much can be also done by small multidisciplinary teams working with local communities. Importantly such teams are most effective where they include members of the target audience for the health promotion initiative. Consequently where the health of mothers and children is the priority, to engage the target audience effectively, parents and family members including children should contribute as members of the team. Worldwide, education of girls is known to generate multiple health and economic benefits; measures to counter misinformation and use of education programs such as the WHO health promotion model to provide knowledge accompanied by practical health-related skills are of proven value. Effective teams incorporate cultural traits and gender equity into strategies that build resilience and self-regulatory efficacy over social determinants of health. Strategies that help individuals and communities to advance towards the UN sustainable development goals have obvious merit. Health knowledge can be conveyed readily, for example in relation to childhood vaccination, but achieving changes in values, attitudes, and health habits requires effort and innovation by multidisciplinary teams that work synergistically to promote health in an innovative and inclusive manner. The more this is done, the greater the beneficial changes we are likely to achieve.